2000
DOI: 10.1073/pnas.97.21.11307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eight growth factors on the differentiation of cells derived from human embryonic stem cells

Abstract: Human embryonic stem (ES) cells are pluripotent cells derived from the inner cell mass of in vitro fertilized human blastocysts. We examined the potential of eight growth factors [basic fibroblast growth factor (bFGF), transforming growth factor ␤1 (TGF-␤1), activin-A, bone morphogenic protein 4 (BMP-4), hepatocyte growth factor (HGF), epidermal growth factor (EGF), ␤ nerve growth factor (␤NGF), and retinoic acid] to direct the differentiation of human ES-derived cells in vitro. We show that human ES cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
637
4
32

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,026 publications
(681 citation statements)
references
References 22 publications
8
637
4
32
Order By: Relevance
“…This is somehow in contrast with the fact that in developing embryos, HNF-6 is expressed in a lineage-restricted manner [17]. However, several lineage-restricted factors, which include HNF-1α, HNF-1β and PDX-1 [29,34,35], are known to be expressed in undifferentiated ES cells and we show here that this is also the case for NGN-3. More importantly, we found that HNF-6 is also expressed in the outer layer of the EBs, which is consistent with the known expression of HNF-6 in the yolk sac [36].…”
Section: Discussioncontrasting
confidence: 58%
“…This is somehow in contrast with the fact that in developing embryos, HNF-6 is expressed in a lineage-restricted manner [17]. However, several lineage-restricted factors, which include HNF-1α, HNF-1β and PDX-1 [29,34,35], are known to be expressed in undifferentiated ES cells and we show here that this is also the case for NGN-3. More importantly, we found that HNF-6 is also expressed in the outer layer of the EBs, which is consistent with the known expression of HNF-6 in the yolk sac [36].…”
Section: Discussioncontrasting
confidence: 58%
“…In addition to this self-renewal ability, hESCs differentiate both in vivo and in vitro, generating representatives of all three embryonic germ layers, including neural progenitors, cardiomyocytes, trophoblast cells, endothelial cells, hematopoietic lineages, hepatocyte-like cells, osteoblasts, and insulin-expressing cells [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Because of these fundamental characteristics, hESCs hold promise for cell-based therapies for degenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…See, for instances, the papers of Heo et al [20], Eiselleova et al [21], Chung et al [22], and Schuldiner et al [23]. More generally, other conditions such as the level of oxygen, or of nutrients such as glucose, can also affect the growth of stem cells, as demonstrated in works such as [24,25,26].…”
Section: Modeling Proliferative Index Of Mesenchymal Stem Cellsmentioning
confidence: 99%